Adaptive TTL based Approach to Balance DNS Server Load - Mackus, T.; Simonaitis, T.; Tamulioniene, D. (Elektronika ir Elektrotechnika, 2012)
This paper presents analysis of Domain Name System (DNS) resource records (RR) “time-to-live” (TTL) values at authoritative DNS server to balance DNS query rate at the desired level. According to the research and experiment results adaptive TTL value can be effectively used to manipulate incoming DNS query rate. Ill. 5, bibl. 11 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1058